A Mutation Testing Analysis And Regression Testing (International Journal of Engineering and Computer Science, 2017)
Software testing is an investigation conducted to provide stakeholders with information about the quality of the product or service under test. Software testing can also provide an objective, independent view of the software to allow the business to appreciate and understand the risks of software implementation. In this paper we focused on two main software testing –mutation testing and mutation testing. Mutation testing is a structural testing method, i.e. we use the structure of the code to guide the test process. A mutation is a small change in a program. Such small changes are intended to model low level defects that arise in the process of coding systems. Ideally mutations should model lowlevel defect creation. Mutation testing is a method of software testing in which program or source code is deliberately manipulated, followed by suite of testing against the mutated code. The mutations introduced to source code are designed to imitate common programming errors. A good unit test suite typically detects the program mutations and fails automatically. Mutation testing is used on many different platforms, including Java, C++, C# and Ruby. Regression testing is a type of software testing that seeks to uncover new software bugs, or regressions, in existing functional and non-functional areas of a system after changes such as enhancements, patches or configuration changes, have been made to them. During confirmation testing the defect got fixed and that part of the application started working as intended. But there might be a possibility that the fix may have introduced or uncovered a different defect elsewhere in the software. The way to detect these ‘unexpected side-effects’ of fixes is to do regression testing. The purpose of a regression testing is to verify that modifications in the software or the environment have not caused any unintended adverse side effects and that the system still meets its requirements. Regression testing are mostly automated because in order to fix the defect the same test is carried out again and again and it will be very tedious to do it manually. Regression tests are executed whenever the software changes, either as a result of fixes or new or changed functionality.